The Simple Classroom Method to Demonstrate the Law of Conservation of Mass - Parashar, Renu; Parashar, R. K. (SCHOOL SCIENCE, 2018)
Laboratory methods that are given to verify the law of conservation of mass require an accurate balance and weighed amount of material for performing the activity. Generally, a precipitation reaction is preferred in these activities to show that a chemical reaction has occurred, and verification requires careful mass measurement before and after the reaction. This paper deals with a straightforward and fast method with very low/no-cost involvement and uses environment-friendly materials.